Adopting photovoice to explore teachers’ experiences in online teaching - Bambang Widi Pratolo; Rofiqoh Rofiqoh; Candradewi Wahyu Anggraeni; Diah Safithri Armin (International Journal of Evaluation and Research in Education (IJERE), 2024)
The coronavirus disease 2019 (COVID-19) outbreak has caused a rapid and massive change in the education sector across the world and left no choice to teachers to maintain their status quo. As a country with very diverse geographical and technological conditions, Indonesia has felt the severe impact of this pandemic. This study explores how Indonesian English as foreign language (EFL) teachers struggle to adapt to the online teaching process, identifies the challenges they encountered during the online teaching and learning process, and investigates their strategies in coping with the associated challenges to ensure the learning objectives were achieved. This study employed photovoice as a visual research methodology to capture the new phenomena and answer the research objectives by inviting four English teachers from three different islands, Java, Sumatra, and Sulawesi to share their experiences and strategies for survival. The results indicated that Indonesian EFL teachers suffered from challenging experiences, including the trial and error of learning management system (LMS) choice, and were confronted with unpleasant feedback from the students. This study also identified poor internet connection and low online student participation as the main issues. To deal with such problems, especially with low student participation, they viewed disadvantaged situations as a trigger to improve their creativity.